LITERAL TRANSLATION IN “BOHEMIAN RHAPSODY” FILM - Fanny Fitri Kharizna; Mayasari . (Jurnal Education and Development, 2021)
The problem of the study in this research how often is the use of Literal translation in Bohemian Rhapsody film and how is the influence/effect of Literal Translation to the audience/reader in the Bohemian Rhapsody film. Then, the informants of this research was descriptive method, using quantitative approach. According to Sugiyono (2013) descriptive research is a research that describe a phenomenon, events either using quantitative and qualitative data. It aimed to give the description about Literal Translation and how is the influence/effect of it the the audience/reader. Then the informants of this research are people who understand about Literal Translation such as linguists, researchers who took the study of language, and also from books. The results showed that Literal Translation in “Bohemian Rhapsody” film that the translator using Literal Translation method is easy to understand and is very often used in translation. The meaning in Literal Translation is to help the writer to communicate by using second language with a community which is considered not to speak the same language.